2007
DOI: 10.1080/09540120701294278
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences among third agent HIV medications: a US and German perspective

Abstract: The objective is to assess patient preferences for attributes associated with third agent HIV medications, including fosamprenavir/ritonavir (FPVr), fosamprenavir (FPV), lopinavir/ritonavir (LPVr), atazanavir (ATZ), and efavirenz (EFV). Subjects with HIV were recruited in the US and Germany to complete a computerized adaptive conjoint survey that assessed 13 attributes, including moderate to severe side effects, regimen convenience, drug resistance and efficacy. Literature on the target third-agent HIV drugs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Moreover, our findings were consistent with the finding of no substantial differences observed in relative importance of eleven of 12 side effects between HIV treatment-experienced, who may have experienced treatment side effects, versus treatment-naïve patients. 18 The current study also found that a more convenient administration regimen was more important to patients than severe side effects when the respective risk was less than 13%. Similarly, improved convenience has been found to be influential in treatment choices in other studies.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, our findings were consistent with the finding of no substantial differences observed in relative importance of eleven of 12 side effects between HIV treatment-experienced, who may have experienced treatment side effects, versus treatment-naïve patients. 18 The current study also found that a more convenient administration regimen was more important to patients than severe side effects when the respective risk was less than 13%. Similarly, improved convenience has been found to be influential in treatment choices in other studies.…”
Section: Discussionmentioning
confidence: 69%
“…16 Specifically, Sun et al 16 evaluated preferences for 27 different side effects among patients with ovarian cancer. They found that severe nausea and vomiting was the least preferred toxicity and that "numbness in hands/feet" was among the most 18 Figure 3 Percentages of patients preferring treatments with differences in survival advantage and differences in regimen convenience, holding all other attributes constant.…”
Section: Discussionmentioning
confidence: 99%
“…The technique is widely used in marketing and several fields of economics including health [19,[35][36][37]. Patient preferences for HIV testing [31], HIV vaccines [29] and ART regimens [1] have been reported and although most CA studies are from highincome countries, at least one health CA has been reported from a low-income context [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for adherence levels below this threshold are complex. Several causal relationships have been suggested for suboptimal HIV treatment adherence, including complicated treatment regimens, patient-specific factors and treatment-related adverse events (AEs) [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%